Evaluation of scar revision after inadequate primary excision of cutaneous mast cell tumors in 85 dogs (2000–2013). Issue 4 (5th March 2021) - Karbe, Georga T.; Davis, Elizabeth; Runge, Jeffrey J.; Brown, Dorothy C.; Holt, David E.
Abstract: Objective: To determine the frequency of residual tumor, and factors associated with local recurrence and disease progression in dogs with incompletely excised mast cell tumors (MCT) following scar revision surgery. Study Design: Retrospective study. Animals: Eighty‐five dogs. Methods: Medical records from January 2000 to April 2013 were reviewed. Dogs with scar revision surgery after incomplete primary MCT excision were included. Recorded were signalment; initial tumor size, location and grade; time interval between primary excision and scar revision surgery; presence of MCT in the resected scar; local recurrence, lymph node metastasis, systemic metastasis, and cause of death. Results: Eighty six tumors in 85 dogs were studied. Residual MCT was found in 23 (27%) resected scars. Seven (8%) scars with residual MCT had incomplete or narrow margins. Follow‐up was available for 68 dogs (69 tumors; median 403 days; range 4–2939). Local recurrence was reported in three (4%) dogs at 212, 555, and 993 days. Disease progressed in 10 dogs (14.5%) with regional or systemic metastasis at a median of 207 days (64–1583). Margin status and presence of MCT in the resected scar were not associated with local recurrence or disease progression. Lymph node metastasis ( p = .004), locoregional recurrence ( p = .013), and disease progression ( p = .001) were significantly more likely in Grade III tumors. Conclusion: Twenty‐seven percent of resected scars contained residual MCT, but recurrence was uncommon after surgical revision. Clinical significance: Clinicians should primarily consider tumor grade when estimating the likelihood of local recurrence and disease progression and determining the need for ancillary treatment of MCT after scar resection.